Psychological distance and user engagement in online exhibitions: Visualization of moiré patterns based on electroencephalography signals - Li, Jingjing; Yang, Ye; Zhang, Zhexin; Yoshida, Nozomu; Xanat, Vargas Meza; Ochiai, Yoichi (Frontiers in Psychology, 2022)
The COVID-19 pandemic has significantly affected the exhibition of artworks in museums and galleries. Many have displayed their collection online. In this context, experiencing an online exhibition is essential for visitors to appreciate and understand the artwork. Compared with offline exhibitions, visitors to online exhibitions are often unable to communicate their experiences with other visitors. Therefore, in this study, by facilitating communication via a Zoom call, we established a system that allows two people to visit the museum together through the Google Arts & Culture (GA&C) website. To reduce the psychological distance between online visitors and help increase user engagement, we designed and developed a media device based on moiré pattern visualization of electroencephalography (EEG) signals. The participants were divided into two groups to visit the online museum, communicating remotely through Zoom. The objective of this study was to test whether a real-time EEG signal visualization device could help close the psychological distance between participants and whether it could increase user engagement with the online exhibition. Participants were randomly assigned to either the normal online exhibition experience (NOEE) group or the EEG signal visualization device (ESVD) group. Participants in the NOEE group experienced four online exhibitions (Task1, Task2, Task3, Task4) together (two participants per test unit). The conditions for participants in the ESVD group remained the same, apart from adding a media device to enable them to visualize EEG signals. A total of 40 university students participated in this study. Independent samples t-tests revealed that participants in the ESVD group perceived a significantly closer psychological distance between themselves and the participants on the opposite side than those in the NOEE group (t=-2.699; p=0.008<0.05). A one-way ANOVA revealed that participants experienced Task3 with significantly closer psychological distance assessments than Task1 (P=0.002<0.05), Task2 (P=0.000<0.05), and Task4 (P=0.001<0.05). Repeated ANOVAs revealed that participants in the ESVD group had higher overall user engagement than those in the NOEE group, with marginal significance (P=0.056<0.1). Thus, this study shows that EEG visualization media devices can reduce the psychological distance between two participants when experiencing an online exhibition. Moreover, it can increase user engagement to some extent.